Development of Canva-based learning media for the Mathematics subject of fractional numbers - Feladi, Vindo; Debora, Tasya Pricilia; Firanda, Yagi; Patrisia, Katarina; Sari, Ceni Febi Kurnia (Research in Education and Technology (REGY), 2023)
Students often have difficulty learning just by reading books. Mathematics is also one of the major difficulties for some students. For students to more easily understand the material, Canva-based learning media was created. Canva is an application that can be developed in the process of making Mathematics learning media, which needs media as an introduction to information from abstract learning material content. The Canva application provides a variety of interesting features that can make it easier for educators to create learning media, one of which is the availability of various templates that can be used in the process of designing learning media, one of which is Mathematics in MI/elementary school. This Canva-based learning media was created with the aim that students don’t get bored easily and can more easily learn while playing. The method used in this research was demonstration learning by making it easier for students to learn independently. The instrument used in this research was a questionnaire. The research subjects consisted of 1 media expert, 1 material expert, and 18 students of the Information Technology Education Study Program, IKIP PGRI Pontianak. The test results showed that Canva-based learning media for Mathematics Subjects was declared feasible and can be applied to Mathematics Subjects with Fractional Operation Materials.